2020
DOI: 10.21203/rs.3.rs-71503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High phosphate levels promote muscle atrophy via myostatin expression in differentiated L6 myotubes

Abstract: Background: Sarcopenia is the age-induced, progressive loss of skeletal muscle mass and function. This phenomenon is observed in patients with chronic kidney disease (CKD). However, the intracellular mechanism underlying the progressive sarcopenia in CKD has not been completely elucidated. Although hyperphosphatemia contributes to cellular senescence, it is unclear whether this condition induces skeletal muscle atrophy. The aim of this study was to determine the effect of hyperphosphatemia on skeletal muscle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In line with our observations, growing evidence supports a correlation between higher serum Pi and lower muscle strength. Our present and previous in vitro studies have demonstrated that rodent muscle cells cultured in a high-Pi-containing medium exhibit muscle atrophy characterized by the accumulation of myostatin, accelerated senescence with integrin-linked kinase overexpression, reduced proliferative capacity, activation of autophagy, reductions in mitochondrial membrane potential, and activation of Nrf2 signaling [ 35 , 36 , 37 , 38 ]. Furthermore, increased Pi can reduce Ca 2+ release from the sarcoplasmic reticulum, which may lead to reduced cross-bridge activity and impaired muscle contraction [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 79%
“…In line with our observations, growing evidence supports a correlation between higher serum Pi and lower muscle strength. Our present and previous in vitro studies have demonstrated that rodent muscle cells cultured in a high-Pi-containing medium exhibit muscle atrophy characterized by the accumulation of myostatin, accelerated senescence with integrin-linked kinase overexpression, reduced proliferative capacity, activation of autophagy, reductions in mitochondrial membrane potential, and activation of Nrf2 signaling [ 35 , 36 , 37 , 38 ]. Furthermore, increased Pi can reduce Ca 2+ release from the sarcoplasmic reticulum, which may lead to reduced cross-bridge activity and impaired muscle contraction [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 79%
“…In differentiated C2C12 myotubes, phosphate induces oxidative stress and impairs mitochondrial function [255]. Furthermore, in L6 myotubes phosphate decreases the expression levels of myosin heavy chain, increases myostatin expression, and elevates caspase-3 activity in a dose-dependent manner, indicating that phosphate downregulates protein synthesis and upregulates protein degradation and induces atrophy and cell death [273]. Furthermore, phosphate induces atrophy in L6 myotubes by activating autophagy [274].…”
Section: Phosphate and Sarcopeniamentioning
confidence: 99%